2017
DOI: 10.1038/srep41854
|View full text |Cite
|
Sign up to set email alerts
|

Toxic metabolites, MAPK and Nrf2/Keap1 signaling pathways involved in oxidative toxicity in mice liver after chronic exposure to Mequindox

Abstract: Mequindox (MEQ) is a synthetic antimicrobial agent of quinoxaline-1,4-dioxide group (QdNOs). The liver is regarded as the toxicity target of QdNOs, and the role of N → O group-associated various toxicities mediated by QdNOs is well recognized. However, the mechanism underlying the in vivo effects of MEQ on the liver, and whether the metabolic pathway of MEQ is altered in response to the pathophysiological conditions still remain unclear. We now provide evidence that MEQ triggers oxidative damage in the liver. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 73 publications
3
54
0
Order By: Relevance
“…In the present study, an accuracy error threshold of ±20 ppm was set as a limit to the calculation of possible elemental compositions. The identification of MEQ and its metabolites were also based on the recent reports ( Huang et al, 2015 ; Liu et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, an accuracy error threshold of ±20 ppm was set as a limit to the calculation of possible elemental compositions. The identification of MEQ and its metabolites were also based on the recent reports ( Huang et al, 2015 ; Liu et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…A large amount of evidence has suggested that the N →O group reduction is a major concerned metabolic pathway of QdNOs ( Cheng et al, 2015 , 2016 ; Liu Q. et al, 2016 ); accompanying this, some ROS and radical intermediates have emerged that ultimately cause oxidative stress ( Liu et al, 2017 ). It was revealed that oxidative stress plays a critical role in the damage caused by QdNOs such as apoptosis, DNA and lipid damage in vitro and in vivo ( Chowdhury et al, 2004 ; Azqueta et al, 2007 ; Yang et al, 2013 ; Zhang et al, 2014 ; Wang et al, 2015 ; Liu et al, 2017 ). The genotoxicity induced by QCT, OLA and MEQ was found to be closely related to oxidative stress ( Zou et al, 2009 ; Huang et al, 2010 ; Liu W.Y.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations